Creating shared value: Investigating how micro-property developers in townships can collaborate with impact investors - Ngakane, Boipelo (Graduate School of Business (GSB), 2023)
Micro-property developers are social entrepreneurs operating in townships and offer high quality rental units that upholds the dignity of community members. Although they are making a valuable contribution they are also faced with many challenges and the biggest being access to funds. This study looks at how impact investing, an emerging funding model can be used to address this challenge. Impact investing can be described as a cross-sectional initiative that involves the professional participation of various stakeholders; to drive social entrepreneurship to a level which can drive the socio-economic impact within communities, to create a social good that optimises financial, social and environmental returns ( Annual Impact Investor Survey, 2019). This research study seeks to explore and understand collaboration strategies that can be employed by micro-property developers in the context of South African townships. This study investigates how micro-property developers, through institutional systems and a multi-stakeholder approach can collaborate with impact investors by applying the concept of collective impact effort in township areas. Further on, this study highlights the importance of impact investing and unpacks the successes and challenges in township areas by illuminating how risk-taking, organisational values and funding contribute to corporate considerations in generating measurable, social and environment impact combined with financial return. Through relevant literature consulted and the use of in-depth interviews this study adopted a qualitative research methodology. Research participants included micro-property developers, impact investors and intermediaries. The research findings indicate that in the corporate ambit of social entrepreneurship and impact investing; variables such as income, risks, impact measurement, the situated area of human settlement and investor readiness are key considerations in the successful acquisition of funding opportunities. In addition, although impact investment in township areas is still an untapped market in South Africa, community leadership and partners should equally advocate the need of inclusion and innovation to steer sustainable impact investment opportunities in such communities. This study suggests that impact investors and funders should work toward cross-sectional initiatives that are scalable and inclusive, and that can create a positive impact in township communities. This study also recommends that a level of deeper knowledge is required through informed research, to understand the value and the impact of impact investments in township areas. This way, scientific data can override all stereotypical notions linked to township investments, as stigmas of crime and risks still hinder investment opportunities in townships compared to their urban counterparts.